2014
DOI: 10.1111/1440-1681.12304
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine as a probing tool for the mechanistic study of acupuncture treatment

Abstract: To date, acupuncture has been widely used despite a lack of solid clinical evidence in the East and West. However, there are few validated in vitro models for the mechanistic studies of acupuncture. We hypothesized that adenosine could be used as a probing tool in the mechanistic studies of acupuncture because of its critical role in the action of acupuncture. Subsequently, we tested this hypothesis using both in vitro and in vivo experiments. First, we found that adenosine stimulation mimicked the effect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Interestingly, recent studies demonstrated a role for A 1 receptors in the mediation of the antinociceptive effect of acupuncture, whose analgesic effect has been replicated by direct injection of an A 1 receptor agonist [66,67]. In particular, A 1 activation has been shown to mimic the effect of acupuncture on miRNA profiling and protein levels [68].…”
Section: Adenosine and Painmentioning
confidence: 99%
“…Interestingly, recent studies demonstrated a role for A 1 receptors in the mediation of the antinociceptive effect of acupuncture, whose analgesic effect has been replicated by direct injection of an A 1 receptor agonist [66,67]. In particular, A 1 activation has been shown to mimic the effect of acupuncture on miRNA profiling and protein levels [68].…”
Section: Adenosine and Painmentioning
confidence: 99%
“…Thus, EA can alter the expression of NR1 and TRPV1 in hippocampal CA1 areas in middle cerebral artery occlusion rats [27]. In addition, EA can inhibit long-term potentiation in the SC dorsal horn of rats after nerve injury [28]. We found that pNR1 but not pNR2B was significantly activated by both MA and different frequencies of EA.…”
Section: Discussionmentioning
confidence: 66%
“…Spontaneously hypertensive rats were used and acupuncture at acupoint LR3 was given to each rat. The result confirmed that adenosine stimulation mimicked the effects of acupuncture and miR-339, miR-223, miR-145 expressions were upregulated in the brain [35]. Acupuncture treatment at nonacupoint was also performed within the same group, and the result showed that increased expression of the miRNAs by acupuncture at acupoint LR3 had not occurred at nonacupoint [36].…”
Section: Main Textmentioning
confidence: 67%